Does sovereign debt ratings news spill over to international stock markets? - Ferreira, Miguel A. (2007)
The evidence here indicates that sovereign debt rating and credit outlook changes of one country have an asymmetric and economically significant effect on the stock market returns of other countries over 1989-2003. There is a negative reaction of 51 basis points (two-day return spread vis-Ã¡-vis the US) to a credit ratings downgrade of one notch in a common information spillover around the world. Upgrades, however, have no significant impact on return spreads of countries abroad. Closeness (e.g., geographic proximity) and emerging market status amplify the effect of a spillover. Downgrade spillover effects at the industry level are more pronounced in traded goods and small industries.